Anatomic pathology data generation in preclinical toxicology evaluation: Troubleshooting and risk management for toxicologists. (10th October 2019) - Neef, Natasha; McInnes, Elizabeth
Highlights: Anatomic pathology endpoints are frequently the most significant element of toxciology. Anatomic pathology data are also among the most subjective endpoints in regulatory toxicology studies. A strategy for minimizing and managing the risk of misdiagnosis/misinterpretation of pathology data is critical. The article provides a sound management strategy for toxicologists without in-house pathology support. Abstract: In routine regulatory toxicology studies, the anatomic pathology endpoints are frequently the most significant element of the study data. They may profoundly influence subsequent clinical development and use of a test article, with implications for both human safety and for the fate of key commercial assets. Unfortunately (in common with other perceptual medical specialties), anatomic pathology data are also among the most subjective endpoints in regulatory toxicology studies - a challenge magnified by the fact that not only the diagnostic data but the anatomic pathologist's interpretation of it in their narrative report represent raw data within a regulated study (United States Federal Register, 1987 ). A strategy for minimizing and managing the risk of misdiagnosis/misinterpretation of pathology data is critical for any preclinical toxicology development program and is a collaborative approach between study directors, study monitors and toxicologists and toxicologic pathologists. The article provides a basic understanding of the sources of error and limitations of anatomic pathology evaluation, a starting point for troubleshooting and a basis for a sound management strategy. It describes common reasons for unexpected or inconsistent pathology findings and sets out to provide a framework for toxicologists to approach commissioning and critically evaluating their pathology data, and for identifying situations where additional third-party advice and review may be justified.